2009
DOI: 10.1186/1751-0759-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gender role, anger expression, thermal discomfort and sleep onset latency in women

Abstract: BackgroundWomen with thermal discomfort from cold extremities (hands and feet; TDCE) often suffer from prolonged sleep onset latency (SOL). Suppressed anger could contribute to the genesis of both TDCE and prolonged SOL. The aim of the study was to test the hypothesis whether stereotypic feminine gender socialization (SFGS) is related to anger suppression (experienced anger inwards, Anger-In), which in turn could affect TDCE and SOL.Methods148 women, a sub-sample of a larger survey carried out in the Canton Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…cold hands and feet, in a Swiss study (Kräuchi et al., 2008; Mozaffarieh et al., 2010). In a follow‐up study, von Arb et al. (2009) suggest that ‘stereotypic feminine gender socialization may play an important determinant for anger suppression, which subsequently can lead to thermal discomfort from cold extremities’.…”
Section: Discussionmentioning
confidence: 99%
“…cold hands and feet, in a Swiss study (Kräuchi et al., 2008; Mozaffarieh et al., 2010). In a follow‐up study, von Arb et al. (2009) suggest that ‘stereotypic feminine gender socialization may play an important determinant for anger suppression, which subsequently can lead to thermal discomfort from cold extremities’.…”
Section: Discussionmentioning
confidence: 99%
“…Another trigger factor is psychological stress [45]. The way our body responds to this stress seems to be individually different [46] and also gender dependent [47]. Subjects with PVD often respond with redistribution of BF.…”
Section: Vascular Dysregulationmentioning
confidence: 99%
“…In glaucoma patients with PVD, we often observed very fast progression of visual field defects during a major stress event, for example, in the context of a divorce. It has recently been shown that women who commonly suppress anger experience more thermal discomfort from cold extremities and have prolonged sleep onset latency [47]. Furthermore, PVD subjects should avoid extensive cold.…”
Section: Therapymentioning
confidence: 99%
“…That glaucoma is associated with psychosomatic components is supported by the observation that women showing FS signs (e.g. cold extremities, prolonged sleep onset latency) have a tendency to suppress anger because of stereotypic feminine gender socialization ( van Arb et al, 2009 ), and normal-tension glaucoma patients show significantly more complaints and emotional instability ( Erb et al, 1999 ).…”
Section: Neurological Influences In “Ocular” Diseasesmentioning
confidence: 99%